1994
DOI: 10.1183/09031936.94.07101877
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to environmental tobacco smoke and risk of lung cancer: the epidemiological evidence

Abstract: E Ex xp po os su ur re e tto o e en nv vi ir ro on nm me en nt ta al l t to ob ba ac cc co o s sm mo ok ke e a an nd d r ri is sk k o of f l lu un ng g c ca an nc ce er r: : t th he e e ep pi id de em mi io ol lo og gi ic ca al l e ev vi id de en nc ce e A number of epidemiological studies have been published since then, and have confirmed this association. The possibility of positive results due to bias has been envisaged; it seems, however, that such bias could not explain the whole excess of lung cancer. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 85 publications
(135 reference statements)
0
52
0
1
Order By: Relevance
“…The effects are further divided into established effects and those for which there is strong, limited or controversial evidence. This classification was decided upon by the authors on the basis of judgement in previous reviews [2,5,6,45,[75][76][77][78][79]. For some health outcomes, relevant evidence has been reported recently and, in these cases, more recent references have been included [46,47,[80][81][82].…”
Section: Health Effects Of Etsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects are further divided into established effects and those for which there is strong, limited or controversial evidence. This classification was decided upon by the authors on the basis of judgement in previous reviews [2,5,6,45,[75][76][77][78][79]. For some health outcomes, relevant evidence has been reported recently and, in these cases, more recent references have been included [46,47,[80][81][82].…”
Section: Health Effects Of Etsmentioning
confidence: 99%
“…A considerable amount of evidence relating ETS exposure to adverse health effects has accumulated since the 1970s [2,5,6,[73][74][75][76][77][78][79]. Some health effects are fairly well established, whereas many suggested effects require further investigation.…”
Section: Health Effects Of Etsmentioning
confidence: 99%
“…3 Studies have reported that such passive smokers have their risk of developing lung cancer increased by 20 to 30 %. 4 The present study therefore had the aim of assessing the main obstetric and perinatal effects of active, passive or activepassive smoking occurring in the maternity ward of a public hospital in São Paulo.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we consider exposure assessment for environmental tobacco smoke (ETS), with emphasis on occupational settings. Substantial research on the adverse health effects of ETS has already accumulated (1)(2)(3)(4). Many of the studies have been directed at exposures in residences and involve the effects of smoking in the household on nonsmoking spouses and children, whereas much less data are available on the effects ofoccupational ETS exposure.…”
mentioning
confidence: 99%